2022
DOI: 10.1186/s12912-022-00820-6
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene knowledge, perception, and self-reported performance among nurses in Kelantan, Malaysia: a cross-sectional study

Abstract: Background Nurses interact with patients 24 hours a day, and this connection has the potential to raise the risk of infection transmission to patients. Nursing plays a vital role in pre-venting healthcare-associated infections (HCAIs) by ensuring that hand hygiene (HH) practises are followed and maintained. The purpose of this study was to evaluate nurses’ knowledge, perceptions, and self-reported HH performance scores, as well as their correlation, in tertiary care hospitals in Kelantan, Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…According to our scatter plot, there was a positive but weak correlation between the knowledge score and perception score (p=0.001), suggesting that the increase in the knowledge score is correlated with the increase in perception score. This mirrored the results of the study done by Abd Rahim and Ibrahim [26], employing the Pearson correlation coefficient; they found a significant positive correlation between…”
Section: Correlation Between Knowledge and Perception Scoressupporting
confidence: 85%
See 2 more Smart Citations
“…According to our scatter plot, there was a positive but weak correlation between the knowledge score and perception score (p=0.001), suggesting that the increase in the knowledge score is correlated with the increase in perception score. This mirrored the results of the study done by Abd Rahim and Ibrahim [26], employing the Pearson correlation coefficient; they found a significant positive correlation between…”
Section: Correlation Between Knowledge and Perception Scoressupporting
confidence: 85%
“…In Qassim, Saudi Arabia, research done during the peak of the COVID-19 pandemic reported that HCWs who received appropriate training on HH were more likely to have moderate/good perceptions [9]. Another study from four different tertiary care centers in Malaysia [26] found a significant positive correlation between HH knowledge and HH perceptions. A recent publication from Denmark [27] focusing on perception and self-reported HH compliance among emergency medical services personnel reported that HCWs' perceptions were extensively influenced by several factors, such as support from the management, availability of HH supplies at the point of use, and having a good role model at the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation